BEACon : a boundary embedded attentional convolution network for point cloud instance segmentation - Liu, Tianrui (2021)
Motivated by how humans perceive geometry and color to recognize objects, we propose a Boundary Embedded Attentional Convolution (BEACon) network for point cloud instance segmentation. At the core of BEACon, we introduce the attentional weight in the convolution layer to adjust the neighboring features, with the weight being adapted to the relationship between geometry and color changes. As a result, BEACon makes use of both geometry and color information, takes instance boundary as an important feature, and thus learns a more discriminative feature representation in the neighborhood. Experimental results show that BEACon outperforms the state-of-the-art by a large margin. Ablation studies are also provided to prove the large benefit of incorporating both geometry and color into attention weight for instance segmentation.